A novel holmium–mercury complex: Structure, green photoluminescence, energy transfer mechanism and semiconducting properties. Issue 7 (July 2019) - Lin, Wei-Sheng; Kuang, Han-Mao; Luo, Hui; Chen, Wen-Tong
The complex (Ho(IA)3 (H3 O)(H2 O)) n (0.5 n Hg2 I6 ) (HIA = isonicotinic acid) has been synthesized via a hydrothermal reaction and has a one-dimensional (1D) chain-like structure. It has an emission band in the green region of 542 nm, which could originate from the 5 S 2 → 5 I 8 transition of the Ho 3+ ion. The compound possesses Commission Internationale de I'Éclairage chromaticity coordinates of (0.2065, 0.4969) and has a wide optical band gap of 2.32 eV, as found by solid-state UV-Vis diffuse reflectance measurements.